Risk allocation of PPP waste to energy projects in Indonesia: A research framework. Issue 1 (September 2020) - Utama, W P; Wibowo, A; Jumas, D Y; Rita, E; Peli, M; Yulcherlina,
Abstract: Public-Private Partnership (PPP) scheme has been widely adopted in both developed and developing countries to fulfill the need of infrastructure facilities such as toll roads and water supply. In Indonesia, another sector that would be feasible to be developed using the scheme is the energy sector through Waste to Energy (WTE) projects. However, the lack of knowledge and experience of public sectors on the PPP field particularly risk-allocation issues may barrier the project success. This paper presents a research framework to develop a model of risk allocation decision making for PPP WTE projects in Indonesia. A combination of qualitative (literature review and semi-structured interview) and quantitative (Delphi survey) research method is utilized to identify critical risk factors in PPP WTE projects. To develop a risk allocation model, an Adaptive Neuro-Fuzzy Inference System (ANFIS) with two outputs (public and private risk share) is proposed. A set of surveys to collect data for training and checking will be distributed to PPP experts representing government and private sectors in Indonesia, while selected WTE projects are used for data testing. The proposed model is a novel approach in risk allocation PPP research and would be useful for local authorities in Indonesia in proposing the WTE project using the PPP scheme.